2016
DOI: 10.1111/ppa.12534
|View full text |Cite
|
Sign up to set email alerts
|

Screening of rice (Oryza sativa) cultivars for resistance to rice black streaked dwarf virus using quantitative PCR and visual disease assessment

Abstract: Rice black streaked dwarf virus (RBSDV) causing rice black streaked dwarf disease is transmitted by the small brown planthopper (SBPH, Laodelphax striatellus) in a persistent propagative manner. The disease is considered among the most destructive in rice production in east and southeast Asia. For sustainable control of the disease, planting resistant cultivars is the most economical and efficient method. The virus content in different rice cultivars was quantified using a TaqMan RT‐qPCR assay under greenhouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Nonviruliferous WBPH ( S. furcifera ), originally captured in Nanjing, China, were reared in glass beakers with rice seedlings in a laboratory incubator at 26 °C with 16 h light/8 h dark. The insects were transferred onto fresh rice seedlings every week 60 .…”
Section: Methodsmentioning
confidence: 99%
“…Nonviruliferous WBPH ( S. furcifera ), originally captured in Nanjing, China, were reared in glass beakers with rice seedlings in a laboratory incubator at 26 °C with 16 h light/8 h dark. The insects were transferred onto fresh rice seedlings every week 60 .…”
Section: Methodsmentioning
confidence: 99%
“…Due to the lack of the standard virus samples for the majority of plant viruses, the precise quantification methods are not available for the majority of plant viruses in most common laboratories, dampening the quantitative detection of plant viruses and thus increasing the risk of their spread and outbreaks of in the fields. Breeding and cultivation of the virus-resistant varieties are critical for controlling plant viral disease ( Hajano et al, 2016 ); however, selection of virus-resistant varieties during breeding programs also requires the straightforward quantitative methods for detecting the viruses and evaluating the virus resistance of breeding materials ( Picó et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…We focused on BLB because it is a devastating disease and greatly reduces the yield and quality of rice. Reports have shown that a mild BLB infection can reduce the yield by up to 20%, whereas severe infection reduces the yield by up to 50% [ 41 ]. The rate of infection of BLB depends on the strain, rice cultivar, geographical location, stage of plant growth, and seasonal variations [ 42 ].…”
Section: Discussionmentioning
confidence: 99%